Chain effect of lifecourse reproductive characteristics and body fat and muscle on cardiovascular disease in women: a Mendelian randomization study - Dong Liu; Chun Dou; Chaojie Ye; Lijie Kong; Zheng Zhu; Mingling Chen; Jie Zheng; Min Xu; Yu Xu; Mian Li; Zhiyun Zhao; Jieli Lu; et al. (Cardiovascular Diabetology)
Abstract Background Delineating the causal chain effects of reproductive traits and fat- and muscle-related traits on cardiovascular disease (CVD) is essential for optimizing precision prevention and control of cardiovascular health in women. Methods In this study, we applied the two-sample Mendelian randomization (MR) analyses and two-step MR framework to investigate the causal chain effects and the mediating effect pathways among reproductive factors and fat- and muscle-related traits on CVD outcomes in women, applying the genome-wide association study summary statistics of 16 women's reproductive traits across puberty and pre-pregnancy, pregnancy and postpartum, and menopausal transition stages, 16 women's fat- and muscle-related traits, and five CVD outcomes of coronary artery disease (CAD), myocardial infarction (MI), heart failure, atrial fibrillation, and ischemic stroke (IS) from over one million individuals of European descent. Results The MR analyses revealed the associations of genetically predicted nine reproductive traits (i.e., age at menarche [odds ratio (OR) for CAD: 0.92], age at first sexual intercourse [AFS; 0.71], age at first birth [AFB; 0.89], hypertensive disorders of pregnancy [HDP; 1.21], pre-eclampsia [PE; 1.34], preterm birth [PTB; 1.09], sex hormone-binding globulin [SHBG; 0.73], bioavailable testosterone [BT; 1.17], and number of stillbirths [OR for IS: 2.14]) and 13 fat- and muscle-related traits with at least one of five CVD outcomes. Two-step MR identified 30 causal pathways where AFS, AFB, HDP, PE, PTB, SHBG, and BT mediated the effects of body composition on five CVD outcomes, and nine pathways where waist-to-hip ratio, trunk-trunk fat ratio, abdominal subcutaneous adipose tissue, and gluteofemoral adipose tissue mediated the effects of reproductive traits on CAD and MI. Conclusions Lifecourse reproductive characteristics and fat- and muscle-related traits manifested reciprocal mediating effects on CVD, informing targeted strategies for bridging cardiovascular health inequalities in women.